EFFICACY OF HERBICIDES FOR WEED MANAGEMENT IN BERSEEM - BRAJKISHOR PRAJAPATI,; THANGJAM C. SINGH,; PRAVAMANJARI GIRI,; KEWALANAND, (The Bioscan, 2015)
The experiment was conducted during winter seasons of 2011-12 and 2012-13 at G.B.Pant University of Agriculture & Technology, Pantnagar to evaluate suitable herbicide for the control of weeds in berseem. Among herbicidal treatments the weed dry weight was significantly less (48.73 g/0.25m2) due to application of Pendimethalin @ 1.0 kg a.i./ha + Imazethapyr @ 0.15 kg a.i./ha applied immediate after 1st cut resulting in higher weed control efficiency (43.53 %). The green forage (2283.80 q/ha),dry forage (319.30 q/ha) and crude protein yield (75.99 q/ ha) was significantly more due to Imazethapyr @ 0.15 kg a.i./ha applied immediate after 1st and 2ndcut but seed yield was significantly more due to Oxyflourfen @ 0.10 kg a.i./ha + Imazethapyr @ 0.15 kg a.i./ha (Immediate after 1st cut) i.e. 6.75 q/ha compared to remaining herbicidal treatments.This indicates the application of broad spectrum post-emergence herbicides like imazethapyr should be applied twice after 1st and 2nd cut for higher fodder and crude protein yield, while for seed production it need to be combined with pre-emergence herbicides like oxyflourfen and applied once before 1st cut.